The Effects of Precrack Angle on the Strength and Failure Characteristics of Sandstone under Uniaxial Compression. (14th October 2021) - Zhang, Shuai; Xu, Jinhai; Chen, Liang; Shimada, Hideki; Zhang, Mingwei; He, Haiyang
Abstract : Characterization of the mechanical properties of cracked rock masses is essential for ensuring the long-term stability of the engineering environment. This paper is aimed at studying the relationship between the strength characteristics of specimen and the angle of precrack, as well as the interaction of cracks under uniaxial compression. To this end, two sandstone specimens, distinguished with a single and three precracks, were built using the PFC software. For the former case, both the peak strength and elastic modulus increase to a peak value as the crack angle α gets closer to the forcing (loading) direction. For the latter case, the strength experiences a trend of increasing-maintaining trend as the crack angle α gets closer to the forcing direction, and the elastic moduli are barely affected. For the specimens containing a single precrack, their crack numbers increased approximately in a one-step or two-step stair pattern with increasing axial strain; whereas for the specimens containing three cracks, their crack numbers all showed a multistep growth trend. Furthermore, the failure mode of the specimen is closely related to the precrack angle. However, if the precrack distribution does not affect the original crack propagation path, it will hardly affect the mechanical properties of the specimen.